Implementing Green Human Resource Management in Local Government: Evidence from Bogor City, Indonesia - Tetty Kurniati; Edah Jubaedah; Eris Yustiono; Euis Nurmalia (Trescode Green Organization, 2026)
The growing urgency of environmental sustainability has increased the importance of integrating green principles into organizational management, particularly within the public sector. This study examines the implementation of Green Human Resource Management (GHRM) in the Bogor City Government, Indonesia, and assesses its current state and improvement strategies. Employing a qualitative descriptive approach, data were collected through in-depth interviews with key informants from several local government agencies, complemented by document analysis and field observations. The study analyzes five core dimensions of GHRM: green recruitment and selection, green training and development, green performance management, green compensation and rewards, and green employee involvement. The findings reveal that GHRM implementation in Bogor City remains partial, implicit, and largely informal. Although initiatives such as digitalization, eco-office practices, and employee participation in environmental activities are evident, green principles have not been systematically integrated into formal human resource policies. Major challenges include limited environmental competencies among civil servants, the absence of environmental indicators in performance appraisal systems, and weak incentive mechanisms. This study contributes to the literature on sustainable public management by highlighting micro-level human resource challenges in developing-country contexts and offers practical recommendations to institutionalize GHRM for strengthening organizational sustainability and public service quality.